Analysis of Obedience Factors of Distribution Facilities in Distributing Cosmetics in East Java - Agustina, Pipin Eri; Pristianty, Liza; Rochmah, Thinni Nurul (Universitas Aisyah Pringsewu, 2022)
Cosmetics that have no Marketing Authorization Number (MAN) can harm people's health. This study aimed to analyze the factors that affect the obedience of cosmetics distribution facilities in distributing cosmetics that have MAN in East Java-based on Niven's theory (understanding the instructions, quality of interaction, beliefs, attitudes, personality, social isolation) and Milgram's theory (the status of the facilities, personal responsibility, the legitimacy of authority figures, the status of authority figures, peer support, the proximity of authority figures). This study was a cross-sectional study, using a validated questionnaire. 179 participants were chosen using simple random sampling. The data were analyzed using Partial Least Square (PLS) (p= 0.05). The factor based on Niven's theory that has a significant relationship with obedience is personality (p=0.001). The factors based on Milgram's theory that have a significant relationship with obedience are the legitimacy of authority figures (p=0.025) and peer support (p=0.000). Whereas, understanding the instructions, quality of interaction, beliefs, attitudes, social isolation, the status of facilities, personal responsibility, the status of authority figures, and the proximity of authority figures have no correlation. Milgram’s theory more affects obedience than Niven’s theory. Various kinds of education and monitoring evaluation of distribution facilities were implemented to improve obedience. Abstrak: Kosmetik merupakan salah satu kebutuhan penting tetapi juga dapat membahayakan kesehatan apabila kosmetik tersebut tidak memiliki nomor izin edar. Penelitian ini bertujuan untuk menganalisis faktor kepatuhan sarana distribusi dalam mengedarkan kosmetika yang memiliki nomor izin edar di Jawa Timur berdasarkan Teori Niven (pemahaman tentang instruksi, kualitas interaksi, keyakinan, sikap, kepribadian, isolasi sosial) dan Teori Milgram (status sarana, tanggungjawab pribadi, legitimasi figur otoritas, status figur otoritas, kedekatan figur otoritas). Jenis penelitian observasional dengan desain studi cross sectional. Jumlah sampel sebanyak 179 responden dipilih secara simple random sampling. Instrumen penelitian adalah kuesioner yang sudah divalidasi. Analisis data statistik menggunakan Partial Least Square (PLS) (p= 0.05). Faktor berdasarkan Teori Niven yang mempengaruhi kepatuhan adalah kepribadian (p=0,001). Faktor berdasarkan Teori Milgram yang mempengaruhi kepatuhan adalah legitimasi figur otoritas (p=0,025) dan dukungan rekan (p= 0,000). Sedangkan pemahaman tentang instruksi (p=0,513), kualitas interaksi (p=0,860), keyakinan (p=0,064), sikap (p=0,597), isolasi sosial (p= 0,333), status sarana (p=0,504), tanggungjawab pribadi (p=0,707), status figur otoritas (p=0,060), dan kedekatan figur otoritas (p=0,072) tidak memiliki hubungan signifikan terhadap kepatuhan. Teori Milgram lebih mempengaruhi kepatuhan daripada Teori Niven. Upaya untuk meningkatkan kepatuhan dilakukan melalui berbagai macam edukasi dan evaluasi monitoring sarana distribusi kosmetika.